Interspecies Solidarity: Review of Kendra Coulter, Animals, Work and the Promise of Interspecies Solidarity - Birke, Lynda (Humanimalia, 2016)
Kendra Coulter, Animals, Work and the Promise of Interspecies Solidarity. Basingstoke: Palgrave Macmillan, 2016. 201 pp. $110.00 (hc), 79.00 (e-book).